Scale parameter recognition of blurred moving image based on edge combination algorithm. (27th June 2022) - Lv, Dongbo
In order to overcome the problems of the traditional fuzzy motion image scale parameter recognition method with high recognition error and poor denoising effect, the paper proposes a new fuzzy motion image scale parameter recognition method based on edge combination algorithm. A fuzzy moving image denoising method based on fuzzy wavelet threshold denoising is used to remove noise in the blurred moving image. The scale parameter of the blurred moving image after denoising is extracted through the blurred moving image degradation model. According to the scale parameters of the blurred moving image, the edge combination algorithm is used to realise the recognition of the scale parameters of the blurred moving image. Experimental results show that the proposed method has the best quality of the blurred motion image after denoising, the lowest misrecognition rate of the scale parameter of the blurred motion image, and the application performance is remarkable.